18th International Conference on Aerospace Sciences and Aviation Technology ASAT-18. (September 2019) - Unknown
Abstract : List of Contents, Preface, Program of ASAT-18, Conference Venue, Location of Conference Sessions, Contributors, Conference Committees, Reviewers, Opening Lecture, Invited Speakers, Program of Scientific Sessions, Abstracts of Scientific Papers, Program of Workshops, Exhibition, Authors Index are available in the pdf.